Tolerance in Modernity. From «Utopia» to Locke’s liberal perspective - Villar Ezcurra, Alicia (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Tolerance, one of the most valued virtues in the democratic societies, also can turn into defect in its excess. For this reason, it is advisable to specify the meaning that tolerance had in some of the modern authors who become experienced in the subjects. In this article, after remembering some of the ideals of Utopia according to Tomas Moro and Spinoza, defends the religious tolerance researched by Locke from a liberal perspective. Locke used numerous arguments supporting tolerance furthermore, anticipation of criticism from different authors allowed for concrete support of his views. Like Spinoza, Locke will defend tolerance on behalf of rationality, but he will also appeal to the Christian religion demands and to the use of a tolerance attitude, as a means to maintain a pacific coexistence. Although the modern philosophers’ approaches should be completed, most of the arguments used to defend the moral and prudential value of tolerance, continue being a constant feature in the actual debates.
Keywords: tolerance; freedom; religion; liberalism; justice; virtue; Locke